BENTUK KERJASAMA GURU BK DENGAN WALI KELAS DALAM MENGATASI MASALAH BELAJAR PESERTA DIDIK DI SMA DIAN ANDALAS PADANG - Sari, Ratna - (Bimbingan dan Konseling, 2014)
This study starts from the invisibility of the phenomenon still homeroom yet communicate with a counselor about the problems faced by learners . It is characterized by the presence of counselors who have difficulty in implementing guidance and counseling services sbecause of time constraints and their homeroom to the counselor has not provided information related to the identity , record events and problems that occur in learners . The purpose of this study is to describe:1) Cooperation with the counselor in the administration of activities homeroom guidance and Counseling . 2) Cooperation with homeroom counselor in providing information about the learners . This type of research is classified as descriptive quantitative research . The population is all counselors and high school homeroom Dian Andalas Padang numbered 14 people . Sampling was done in total sampling with a sample size of 14 people. The instrument used in this study was a questionnaire and analyzed by using percentages . The results of this study revealed that counselors cooperation with homeroom in the administration of guidance and counseling activities are in very good criteria and cooperation with homeroom counselor in providing information about the learners are at a very good criterion . It can be concluded that the better cooperation between the counselor and the class teacher will better the teachers in helping to overcome the problem of learners . This research was recommended to counselors and homeroom in order to maintain and increase its cooperation in addressing the problems experienced by learners .